The Pattern of Science Transmission: A Study on Ibnu Hajar al-Asqalani in Teaching and Writing - M. Ma'ruf Misbah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This article aimed to identify the transmission patterns of knowledge carried out by Ibn Hajar al-Asqalani in his intellectual activities. Since the article focused on historical topics, the historical method was applied by analyzing historical facts from its sources. The result obtained was the existence of transmission patterns of knowledge that had been carried out by him in intellectual activities, namely teaching and writing books. Through teaching activities, the target of the transmission of knowledge was the student. Many of his students who later succeeded in becoming scientists who famed. Ibn Hajar al-Asqalani, of course, had a big contribution in delivering them to be scientists. On the other hand, through the activity of writing the book, the target of the transmission of knowledge was the reader. The various books that he wrote had been used as reading material in getting knowledge. As a conclusion, Ibn Hajar al-Asqalani had chosen the most effective pattern in the activity of transmitting knowledge, including patterns that were not bound by time and location.